Pengaruh Brand Ambassador, Brand Image dan Brand Trust Terhadap Keputusan Pembelian Handphone Merek Samsung di Kota Pekanbaru - Fitria Nur Hakiki; Desvi Emti (Yayasan Almanar Pujud, 2025)
This research aims to determine the influence of brand ambassador, brand image and brand trust on purchasing decisions for Samsung brand cellphones in Pekanbaru City. This type of research is quantitative research using multiple linear regression methods. The total sample in this study was 96 respondents who were selected using the purposive sampling method. Data collection was carried out by distributing questionnaires to respondents. Research data was analyzed using the SPSS V.25 program. The results of this research partially show that brand ambassador, brand image and brand trust have a positive and significant influence on the decision to purchase Samsung brand cellphones in Pekanbaru City. Simultaneous test results show that brand ambassador, brand image and brand trust have a positive and significant influence on purchasing decisions for Samsung brand cellphones in Pekanbaru City. The R Square value is 0.535 or 53.5%, indicating that the brand ambassador, brand image and brand trust variables as a whole only have an influence of 53.5% on the purchasing decision variable. Meanwhile, the remaining 46.5% was influenced by other variables not examined in this research.